Differential Remodelling of Endometrial Extracellular Matrix in the Non-Pregnant Uterus of Lagostomus maximus as a Potential Mechanism Underlying Embryonic Death - Francisco Acuña; Gisela Soledad Gualdoni; Francisco Rivollier; Camila Barril; Enrique Leo Portiansky; Claudio Gustavo Barbeito; Elisa Cebral (Animals)
During development, the remodelling of fibrillar components of the uterine extracellular matrix (ECM), mediated by the matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs), plays an essential role in embryonic survival. Previously, we observed that in the plains viscacha (Lagostomus maximus), only caudal implantation sites (IS) contain viable embryos, whereas embryos at cranial and middle IS die and are reabsorbed. The objective of this study was to analyse the distribution and expression of key components of the endometrial ECM, including fibrillar collagens, MMPs 2 and 9, and TIMPs 1 and 2, in three uterine segments (US) of the non-pregnant adult viscachas. In sections from three US, we observed a significant craniocaudal increase in collagen fibres (Van Gieson and Picrosirius red staining) and elastic fibres (Verhoeff-Van Gieson trichrome staining), along with the immunolabelling levels of MMP-2, MMP-9, TIMP-1, and TIMP-2 (immunohistochemistry). Zymography revealed similar gelatinolytic activity of MMP-2 in the three US but higher than the MMP-9 activity. However, MMP-9 activity in the caudal segment was significantly higher than that in the cranial and middle ones. These findings suggest that uterine ECM variations along the craniocaudal axis may contribute to uterine remodelling processes that regulate embryonic survival during gestation.